2008
DOI: 10.3390/ijerph5050356
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins, Furans and PCBs in Recycled Water for Indirect Potable Reuse

Abstract: An assessment of potential health impacts of dioxin and dioxin-like compounds in recycled water for indirect potable reuse was conducted. Toxic equivalency factors (TEFs) for 2,3,7,8-substituted polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDFs) and dioxin-like polychlorinated biphenyls (PCBs) congeners have been developed by the World Health Organization to simplify the risk assessment of complex mixtures. Samples of secondary treated wastewater in Perth, Australia were examined pre-and post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…For these two classes, the concept of toxic equivalents (TEQ) was used, which expresses the toxicities of different chemicals on a common basis by comparing to a reference chemical. This is a widely accepted practice for both PAHs (Bruce et al 2007) and dioxin-like compounds (Van den Berg et al 2006), and the TEQ analysis for these classes are reported elsewhere (Rodriguez et al 2008;Van Buynder et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these two classes, the concept of toxic equivalents (TEQ) was used, which expresses the toxicities of different chemicals on a common basis by comparing to a reference chemical. This is a widely accepted practice for both PAHs (Bruce et al 2007) and dioxin-like compounds (Van den Berg et al 2006), and the TEQ analysis for these classes are reported elsewhere (Rodriguez et al 2008;Van Buynder et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The screening health risk assessment for RO permeate assessed RQs for the 11 chemical classes summarised in Supporting Information Tables S1-S13, plus previously reported risk assessments for dioxins-like chemicals, PAHs, and gross alpha and gross beta particle activity (Rodriguez et al 2008;Van Buynder et al 2009). Table 3 lists all chemicals (16) for which RQ med or RQ max were calculated to be greater than 1.…”
Section: Screening Health Risk Assessment Of Ro Permeatementioning
confidence: 99%
“…Dioxins and furans refer to a class of structurally and chemically related polyhalogenated aromatic hydrocarbons that include polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzo-p-furans (PCDFs) and polychlorinated biphenyls (PCBs) (Kulkarni et al 2008). They are viewed as persistent environmental compounds and their presence has been detected in all compartments of the ecosystem, including water (Rodriguez et al 2008). Kulkarni et al (2008) stated that the presence of dioxins and furans was first reported in fly ash samples by Dutch and Swiss scientists in the year 1977 and 1978 respectively.…”
Section: Dioxin and Furansmentioning
confidence: 99%
“…The most toxic representatives of VOCs are polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs). The US EPA recommends an intake limit of PCDD/F for humans of 0.001 pg/kg bw/day in terms of the most toxic 2,3,7,8-TCDD for a lifetime additional cancer risk of 10 À6 (Rodriguez et al, 2008). The problem of the environmental pollution by PCDD/F arose from the fact that noticeable amount of dioxins was found in the products of municipal solid waste incineration (MSWI) (Tuppurainen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%